THE IMPACT OF THE FORWARD-LOOKING EXPECTED LOSS METHOD REFERS TO FINANCIAL ACCOUNTING STANDARD NO. 71 ON EARNINGS QUALITY OF THE INDONESIAN ISLAMIC BANKS - Eka Marenza, Silvya; Ariskawati, Nur; Laela, Sugiyarti Fatma (Faculty of Economics and Business University of Mataram, 2024)
This research investigates the effect of applying the forward-looking expected loss method as a consequence of Financial Accounting Standard (FAS) No 71 on earnings quality. Since the technique is effective in 2020, forward-looking expected loss is measured using loan loss provisions ratio with a year dummy to differentiate forward-looking and non-forward-looking. At the same time, the predictability of earnings is used as a proxy of earnings quality. The sample consists of 16 Shariah commercial banks from 2018 to 2021, resulting in 55 firm years as a unit of analysis. Using panel data regression, the results show that the higher the reserve for impairment loss of Islamic banks, the lower the quality of earnings. However, after the implementation of SFAS 71, the higher the reserve, the higher the earnings quality, proven by the ability of earnings to predict future earnings.